﻿A differentiated classroom approach for diverse ESL readers - Nooreiny Maarof; ﻿Hamidah Yamat (Universiti Kebangsaan Malaysia, 2010)

(untitled)
﻿Most English as a Second Language (ESL) classroom can be characterized by multifarious factors, which in turn easily define the ESL classroom as the epitome of diversity. This "differentness" of learners poses a great challenge to teachers in providing appropriate instruction in the language skills, such as in the teaching of reading. Reading is a complex skill, which involves the interaction of various factors associated with the reader and the text. Although most ESL readers are literate in their native language, reading in a second language requires specific skills and strategies. In what ways can the teacher assist ESL readers of differing reading abilities to improve their reading skills? How can the teacher manage a class of readers of differing reading abilities? This article discusses an approach which attempts to address the needs of diverse readers. In a differentiated classroom approach, various strategies and activitied task are organized to assist teachers in addressing the differentness of learners in the reading classroom.